Intellectual Property Protection and Drug Plan Coverage: Evidence From Ontario. (October 2018) - Grootendorst, Paul; Shim, Minsup; Falconi, Adam; Robinson, Tyler; Lexchin, Joel
Canada has strengthened intellectual property (IP) protections for pharmaceutical drugs several times over the last 3 decades. This study investigates whether the IP changes had an effect on the market exclusivity time of brand products on the Ontario Drug Benefit (ODB) formulary. We constructed a database that included the first brand approval date for drugs launched between 1974 and 2012, the first ODB listing date of the brand drug, and the first ODB listing date of the generic form of the drug. We then calculated the time of formulary exclusivity to detect any changes in market exclusivity times associated with changes to Canada's IP regimen. There were 595 drugs launched between 1974 and 2012 that were available for analysis. Exclusivity gradually declined from the late 1970s to 1990. Drugs approved in 2004 received 7.6 years of exclusivity, and drugs approved in 2005 received 5 years of exclusivity. Over the time period we analyzed, market exclusivity time of brand drugs experienced marked changes, but we did not detect any systematic effects of Canada's stronger pharmaceutical IP laws on the market exclusivity.